Diagnostic challenges of benign breast phyllodes tumour: A rapid-growing tumour during pregnancy caused breast loss. A case report - Pankratjevaite, Lina (Int J Surg Case Rep, 2021)
INTRODUCTION: Phyllodes tumours are rare breast neoplasms. It is especially rare in pregnancy. PRESENTATION OF CASE: We report a case of a 37-year-old woman with left breast benign phyllodes tumour, which started to grow very fast during pregnancy. The tumour was too big for breast-conserving surgery and it was necessary to remove the whole left breast. Patient underwent successful nipple-skin-sparing mastectomy with immediate silicone implant reconstruction. CONCLUSION: Breast phyllodes are classified as benign, borderline, and malignant. Standard treatment of breast phyllodes is surgery. The choice of surgery type depends on the tumour factors and breast size. We highlight that, inadequate treatment of phyllodes tumour can result to recurrence, growth, or even metastatic spread, when tumour has malignant potential.